Sunflower white blister rust – Host specificity and fungicide effects on infectivity and early infection stages. (January 2015) - Lava, Sukanya S.; Zipper, Reinhard; Spring, Otmar
Abstract: White blister rust is an economically important emerging disease of sunflower caused by Pustula helianthicola . Knowledge on the host range of the pathogen particularly on different Helianthu s species and its relative cultivars is of high relevance for disease management. Natural infection in the field on 13 sunflower genotypes with differentiating resistance against sunflower downy mildew ( Plasmopara halstedii ) showed high susceptibility to P. helianthicola which was independent from the resistance against downy mildew. Similarly, numerous commercial sunflower lines used in Europe showed high susceptibility to white blister rust in the field. Leaf disk inoculation with sporangia of a single spore strain of P. helianthicola confirmed full susceptibility of these genotypes, whereas wild species of Helianthus could not be infected under the controlled conditions except for a single incident observed with Helianthus praecox . Investigation of pre and post penetration events on the leaf surface of selected Helianthus annuus cultivars and wild species revealed that zoospore discharge, encystment and germ tube development occurred similarly on cultivars and wild species. But in the latter no germ tube penetration of the stomata was found and no hyphal or haustoria development was observed after 72–96 hours post inoculation (hpi) in wild species. Studies on the effect of different fungicides showed that the phenylamide metalaxyl-M and the strobilurin azoxystrobin inhibited the infection of seedlings at 1 and 2 μg/mL concentration, respectively, whereas the carboxylic acid amide dimethomorph required ca. a 10 fold higher concentration. With the plant strengthener BABA more than 40% of the plants were infected even at 200 μg/mL treatments. These results corroborated with the effects on early developmental stages of the pathogen (zoospore discharge, encystment, and germ tube development) in host independent experiments. Our results suggest that fungicides provide an effective measure for controlling sunflower white blister rust. However, considering the residual effect of chemicals and the possibility of developing fungicide resistance, breeding for resistant genotypes appears to be a more promising way for long lasting and sustainable disease management. Highlights: Susceptibility of crop sunflower and wild Helianthus species to white blister rust was tested. Several wild Helianthus species showed high resistance to Pustula helianthicola . Resistance to downy mildew does not protect sunflower against white blister rust. Metalaxyl-M and dimethomorph inhibit infection while BABA showed low effects.